Mechanics of spastic muscle and effects of treatment techniques: assessments with intra-operative and animal experiments - Ateş, Filiz. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2013., 2013)
Present thesis is focused on mechanics of spastic human muscles and the e ects of widely used treatment methods in the context of the determinant role of epimuscular myofascial force transmission (EMFT). A novel intra-operative method was developed to measure human Gracilis (GRA) muscle isometric forces with respect to knee angle. In healthy subjects, GRA was shown to have very large operational length range. For spastic cerebral palsy patients on the other hand, GRA muscle did not show abnormal mechanical characteristics: (i) Length range was not narrowed and (ii) high exion forces were not available. Such abnormality occurred if its antagonist vastus medialis is activated simultaneously. Therefore, EMFT mechanism through inter-antagonistic interaction was suggested to determine human muscle characteristics in spasticity. E ects of treatment methods were investigated in animal experiments: (1) Muscle lengthening surgery was shown to a ect (i) proximal and distal sides di erentially and (ii) non-operated neighboring muscle as well. (2) Botulinum Toxin Type-A (BTX-A) administration was shown to change the mechanics of not only the injected but also non-injected muscles in conditions close to in vivo. Additional to active force reductions (i) the narrowed length range of force exertion and (ii) pronounced passive force increase contradictory to the aim were shown. EMFT mechanism was concluded to be determinant for the treatment methods as well.|Keywords : Epimuscular myofascial force transmission, spastic cerebral palsy, intra-operative human experiments, rat anterior crural compartment, muscle lengthening surgery, aponeurotomy, botulinum toxin type-A.
Keywords: Paralysis, Spastic.; Neuromuscular transmission.